A study of flow and heat transfer of nanofluids: between two parallel plates, over a wedge and past a stretching sheet - Gamsha, Abdullahi Madaki (2017)
This thesis investigates analytically and numerically the flow and heat transfer of nanofluids: between two infinite parallel plates, over a wedge, and past a stretching sheet. Two problems have been considered for the parallel plates. A mathematical model of squeezing unsteady nanofluid flow is studied firstly in the presence of thermal radiation, and secondly, in the presence of both thermal radiation and heat generation/absorption. The solutions are obtained by using homotopy perturbation method (HPM) and fourth-order Runge-Kutta with shooting technique (RK4). The flow of nanofluids over a wedge leads to the derivation of the Falkner-Skan equation and this problem have been solved using the optimal homotopy asymptotic method (OHAM). Finally, three issues have been considered for nanofluids past the stretching sheet. Firstly, we considered a problem of flow and heat transfer of nanofluids over a dynamic stretching sheet with non-linear velocity and variable thickness in the presence of Brownian motion and thermal radiation. Secondly, the effect of a chemical reaction is taken into account. These two problems have been investigated using the OHAM and RK4. Lastly, a mathematical model for the effect of chemical reaction in a natural convective boundary-layer flow of nanofluids has been evolved. The HPM with Pade approximation (HPM-Pade) along with RK4 is used to solve the nonlinear governing equations. It is found that the thermal radiation had recorded a significant influence, in which it has been observed that the growing value of the thermal radiation parameter results to the decrease in the temperature profile in the case of squeezing flow problem. Thereby both the thermal boundary layer thickness and temperature profile have substantially risen in the flow and heat transfer over a stretching sheet cases. From the subsequent cases, we also found that the temperature is high due to the increase in both the Brownian motion and the thermophoresis parameters, while the scenario reverses as the nanoparticle concentration only increases with the strengthen thermophoresis parameter and slow down with an increase in the Brownian motion parameter.